2012
DOI: 10.1007/s10800-012-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of the lithium intercalation into nanoparticles of LiCoO2 from an aqueous solution

Abstract: Nanoparticles of lithium cobalt oxide (LiCoO 2 ) were synthesized by means of a citrate sol-gel combustion route. The particles were characterized by scanning and transmission electron microscopies (SEM and TEM), energy-dispersive X-ray spectroscopy, and X-ray diffraction (XRD) measurements. Near spherical nanoparticles of around 100 nm were observed in SEM and TEM micrographs. XRD data indicated that the as-prepared nanoparticles presented pure phase of LiCoO 2 with R-3m symmetry. The kinetics of electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Cyclic voltammogram of ensemble LiCoO 2 NPs immobilized on a regular gold electrode exhibited a pair of current peaks at 0.44/0.41 V (vs Ag/AgCl) in the presence of 1 M LiNO 3 aqueous solution (Figure a). This result was well consistent with previous studies on the aqueous electrochemistry of LiCoO 2 . , This pair of peaks corresponded to the first-order Mott transition from metallic to insulator phase. Our previous work has shown that delithiated Li 1– x CoO 2 (oxidized form) exhibited smaller RI compared with the lithiated state LiCoO 2 (reduced form), and the RI was nearly proportional to the lithiation state (1 – x ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Cyclic voltammogram of ensemble LiCoO 2 NPs immobilized on a regular gold electrode exhibited a pair of current peaks at 0.44/0.41 V (vs Ag/AgCl) in the presence of 1 M LiNO 3 aqueous solution (Figure a). This result was well consistent with previous studies on the aqueous electrochemistry of LiCoO 2 . , This pair of peaks corresponded to the first-order Mott transition from metallic to insulator phase. Our previous work has shown that delithiated Li 1– x CoO 2 (oxidized form) exhibited smaller RI compared with the lithiated state LiCoO 2 (reduced form), and the RI was nearly proportional to the lithiation state (1 – x ).…”
Section: Resultssupporting
confidence: 93%
“…This result was well consistent with previous studies on the aqueous electrochemistry of LiCoO 2 . 32,33 This pair of peaks corresponded to the first-order Mott transition from metallic to insulator phase. Our previous work has shown that delithiated Li 1−x CoO 2 (oxidized form) exhibited smaller RI compared with the lithiated state LiCoO 2 (reduced form), 26 and the RI was nearly proportional to the lithiation state (1 − x).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Three pairs of current peaks can be clearly identified, which are in good agreements with previous reports on LiCoO 2 electrochemistry. , The first peak (0.47/0.44 V vs Ag/AgCl) indicated the first order insulator–metal phase transition . The second (0.62/0.60 V) and third (0.73/0.71 V) peaks were associated with the order–disorder transitions. , The current peaks accompanying the lithiation process were slightly broader and smaller, which was often observed in aqueous solution due to the slow desolvation process. , …”
Section: Resultssupporting
confidence: 89%
“…The synthesis method of LiCoO 2 nanoparticles was adopted from ref . Briefly, a mixture consisting of 1 mM lithium acetate, 1 mM cobalt­(II) acetate, 20 mL of distilled water, and 2 mM citric acid anhydrous was first prepared.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…52 Further values from EIS are in the range 10 À10 to 10 À9 . 53 Larger values have also been obtained, such as 10 À10 to 10 À7 (ref. 54) (PSCA, EIS), 10 À9 (EVS), 55 and 10 À9 to 10 À8 (PITT).…”
Section: Resultsmentioning
confidence: 99%